Sosialisasi Aplikasi “Saga Sehat” pada Kader Posyandu di Tanjung Kamuning Kabupaten Garut - Titi Purwitasari Handayani; Putri Puji Lestari; Nofita Setiorini Futri Purwanto; Siti Nurcahyani Ritonga; Ira Nufus Khaerani; Intan Rina Susilawati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The nutritional status of children under the age of five is an important indicator of health, as young children are a vulnerable group to nutritional health. The growth process is very rapid, namely physical growth and psychomotor, mental and social development, so it is necessary to obtain nutrition from daily food in proper quantities and good quality. The village of Tanjung Kamuning is one of the villages that are in Tarogong Community Health Center work area in Garut district. The unrecorded problems in the village are the results of a structured weighing of the newspapers carried out by the posyandu (integrated service post) cadres that were used as reporting material for the puskesmas. Innovation tool that serves as a monitoring media and a system that acts as a container for storing and managing news data connected to the Internet for ease of access is the application